2001
DOI: 10.1086/321333
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution X‐Ray Spectroscopy and Modeling of the Absorbing and Emitting Outflow in NGC 3783

Abstract: The high-resolution X-ray spectrum of NGC 3783 shows several dozen absorption lines and a few emission lines from the H-like and He-like ions of O, Ne, Mg, Si, and S as well as from Fe XVII-Fe XXIII L-shell transitions. We have reanalyzed the Chandra HETGS spectrum using better flux and wavelength calibrations along with more robust methods. Combining several lines from each element, we clearly demonstrate the existence of the absorption lines and determine they are blueshifted relative to the systemic velocit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
315
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(349 citation statements)
references
References 46 publications
31
315
3
Order By: Relevance
“…Level population ratio wrt. ground which has been pointed out in Kaspi et al (2001). Nonetheless, the density-sensitive line (13.420 Å) of O-like Fe xix is weaker than the ground level absorption lines (13.521 Å and 13.492 Å).…”
Section: Density Diagnostics For the Ionized Outflow In Ngc 5548mentioning
confidence: 75%
“…Level population ratio wrt. ground which has been pointed out in Kaspi et al (2001). Nonetheless, the density-sensitive line (13.420 Å) of O-like Fe xix is weaker than the ground level absorption lines (13.521 Å and 13.492 Å).…”
Section: Density Diagnostics For the Ionized Outflow In Ngc 5548mentioning
confidence: 75%
“…While the iron K emission line exists in almost all X-ray sources , K-line features from silicon have also been commonly observed (Kaspi et al 2001(Kaspi et al , 2002Kallman et al 2009). Young et al (2005) reported the detection of H-like Si absorption lines in MCG 6-30-15 and determined the outflow velocity by measuring the line blueshift.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the study of the warm absorber is being revolutionized with observations from the dispersion gratings onboard Chandra and XMM-Newton which have been able to resolve individual absorption lines from a myriad of metals and charge states in the warm gas (e.g., Kaastra et al 2000;Kaspi et al 2001;Collinge et al 2001;Lee et al 2001;Kaspi et al 2002). Photoionization modeling has then shown that, in many cases, more than one ionization parameter 1 is needed to describe the observed spectrum (e.g, Morales et al 2000;Kaspi et al 2001;Kaastra et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Photoionization modeling has then shown that, in many cases, more than one ionization parameter 1 is needed to describe the observed spectrum (e.g, Morales et al 2000;Kaspi et al 2001;Kaastra et al 2002). Also, the positions of the lines point toward outflow velocities on the order of a few hundred to a few thousand km s −1 .…”
Section: Introductionmentioning
confidence: 99%